Civics studies classes as a scenario for learning and waiting - Hernández, Andrés E. (Universidad Nacional del Litoral, 2022)
This article is intended to review and delve more deeply into some lines of analysis about the ways of inhabiting classrooms in relation to learning experiences and civic education. After gathering academic reflections on school time, we seek to incorporate the category of waiting into the analysis as a way of bringing to light the processes and experiences of power and domination that take place in classrooms. For this purpose, the ethnographic method is adopted as a key piece in the effort to overcome some of the antinomies that are debated in the field of educational research. These reflections are based on field work carried out for a case study in secondary schools[U1] of Argentina.